Silent Crohn's Disease Predicts Increased Bowel Damage During Multiyear Follow-up: The Consequences of Under-reporting Active Inflammation. Issue 11 (November 2016) - Bhattacharya, Abhik; Rao, Bhavana B.; Koutroubakis, Ioannis E.; Click, Benjamin; Vargas, Eric J.; Regueiro, Miguel; Schwartz, Marc; Swoger, Jason M.; Babichenko, Dmitriy; Hartmann, Douglas; Rivers, Claudia R.; Barrie, Arthur; et al.
Abstract : Background: Patients with Crohn's disease (CD) in clinical remission with elevated C-reactive protein (CRP) have been labeled "silent CD" and have increased 2-year hospitalization rates when compared with asymptomatic patients with no biochemical evidence of inflammation. The risk of cumulative bowel damage in patients with silent CD is unknown. Methods: Observational study of patients with CD prospectively followed in a tertiary referral natural history registry. Consecutive patients with CD in clinical remission (Harvey–Bradshaw Index ⩽ 4) with good quality of life (short inflammatory bowel disease questionnaire score ≥ 50), and same day CRP measurement at first encounter, followed for a minimum of 4 years formed the study population. Disease trajectory was determined using change in Lémann Index as a measure of bowel damage. Results: A total of 185 patients with CD (median age 42 years; 51.4% men) were included in the study. CRP elevation was observed in 43 (23%) patients (Silent CD cohort). Majority of them showed worsening disease trajectories based on change in Lémann Index when compared with asymptomatic patients with normal CRP (65% versus 36%, P < 0.0001). Multinomial logistic regression analysis demonstrated that elevated CRP was independently associated with 7-fold higher odds (odds ratio = 6.93, P < 0.0001) of having worse disease trajectories when compared with stable disease trajectories. Conclusions: Two-thirds of patients with CD in clinical remission, while demonstrating elevated CRP, will develop bowel damage over the ensuing years, despite feeling well. These patients with silent CD are an "at-risk" group who warrant further investigation to prevent development of disease-related complications. Abstract : Article first published online 4 October 2016.